The Implementation of Picture Media as an Effort to Introduce EnglishVocabulary to Elementary Students at SD Negeri Palatiga, Baubau City - Darmayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Picture media is one of the educational media that aims to trigger and stimulate the right brain so that the child can receive the information. This community service aims to provide information about learning models that can be used in English learning activities, which aims to make learning more interesting, attractive, creative, and fun. In addition, the purpose of implementing this community service is to train students’ skills, so that they can think critically and to be active in learning English in the class by using picture media. In this community service activity, the servant teaches by using two learning methods, namely the lectures method and the practical method. The results of this activity shows that the students seem more enthusiastic and active during the learning process. Then, their motivation and enthusiasm also arise from the studens themselves to learn English vocabulary.